An institutional analysis of land readjustment in Turkey - Cagdas, Volkan; Linke, Hans Joachim (TAYLOR & FRANCIS LTD, 2021)
Land readjustment is a property formation process which rearranges the geometries of cadastral parcels and immovable property rights thereof in accordance with land use plans. The literature presents several studies which analyze the effectiveness of land readjustment in various countries. This article aims to contribute to the existing work by presenting an analysis for the Turkish case study based on the Institutional Analysis and Development Framework developed by Elinor Ostrom. For this purpose, the organizational procedures and institutional arrangements that frame land readjustment in Turkey are examined. This analysis reveals the areas of possible reform that may facilitate a transparent and accountable, participatory and inclusive, fair and cost-effective development of land.
Keywords: Land readjustment; Institutional development and analysis framework; Turkey; INVOLVEMENT; MANAGEMENT; PROJECTS; PROPOSAL; DUTCH; TOOL; Engineering; Geology; Remote Sensing